Digitalisation in engineering education: practice challenges and opportunities - Evtushenko Oksana; Toporkova Olga; Kokhashvili Natalia; Yankina Elena (E3S Web of Conferences, 2023)
Digitalisation is the current tendency of modern life. It touches upon various spheres of society. This article contributes to this issue undertaking engineering education practice challenges and opportunities. The article aims at developing new insights: 1) by evaluating the importance of digitalization for the educational process, 2) by introducing the theory and methodology of digital transformation of engineering education, 3) by illustrating the implementation of digital tools in engineering practice. The following theoretical methods were used in the study: a method of theoretical analysis, method of generalisation of accumulated experience, survey method, and predictive methods (forecasting), also empirical research methods: observation, modeling, abstraction, comparison, and analysis of the results of students' educational activities. The article describes the successful experience of using digital technologies on the basis of the Department of Foreign Languages, and the analysis of the practice of using digital tools at Volgograd State Technical University. This approach makes a great contribution into revealing challenges and perspectives of engineering education, stimulating its transition from research to practice.